Distribution and habitat characteristics of three sympatric cetacean species in the coastal waters of Matang, Perak, Peninsular Malaysia. Issue 10 (22nd May 2019) - Kuit, Sui Hyang; Ponnampalam, Louisa Shobhini; Ng, Jol Ern; Chong, Ving Ching; Then, Amy Yee‐Hui
Abstract: Coastal cetaceans in Southeast Asia are poorly studied and are particularly vulnerable to anthropogenic threats, especially in intensive fishing grounds. To investigate the distribution and habitat characteristics of cetaceans in the productive coastal waters of Matang, Perak, Malaysia, boat‐based line transect surveys were conducted between 2013 and 2016. The Irrawaddy dolphin ( Orcaella brevirostris ) was most frequently encountered at 3.87 sightings per 100 km, followed by the Indo‐Pacific finless porpoise ( Neophocaena phocaenoides ) at 1.72 sightings per 100 km, and the Indo‐Pacific humpback dolphin ( Sousa chinensis ) at 0.66 sightings per 100 km. The mean group size was largest for humpback dolphins (8.4 individuals), followed by Irrawaddy dolphins (6.4 individuals), and finless porpoises (2.8 individuals). Humpback dolphins exhibited a clustered distribution concentrated mainly in shallow estuarine waters (<10 m deep and <5 km from river mouths), whereas Irrawaddy dolphins were more widely distributed in farther coastal waters (<15 m deep and <15 km from river mouths), and finless porpoises were mostly found farthest from the shore in coastal waters (10–25 m deep and >15 km from river mouths). The spatial distribution of the three cetaceans overlapped minimally, and this is likely to reflect the distribution of preferred prey resources, species interactions, and their differential responses to anthropogenic activities and species dominance. The results from our study serve as baseline information for future research, conservation, and habitat management of these vulnerable and endangered coastal cetaceans. Conservation actions are recommended for the Matang area.